The Impact Of Social Networking On The Values And Behaviors Among University "Face Book" Students Sites Model - Hallak, Boutros (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to identify the impact of social networking on the values and behaviors among university "Face book" Students sites model " To achieve the objectives of the study were a number of questions as follows: 1- What are the main qualitative characteristics of the members of the study sample? 2- What are the habits and patterns of use of university students to the social networking site "Face book 3- What are the main pros and cons of using university students to site "Face book"? 4- Do you use the site "Face book" and exposure to its contents helps university students to link the values? 5- Does it help the site "Face book" university students to overcome some of the negative behaviors. And to answer the questions of the study was the use of a questionnaire included several axes, according to the objectives of the study, and the study included all students enrolled in the University of Damascus community in the year 2016 Aldrase2015- And study sample consisted of 400 single of university students of different scientific specialties, were randomized manner. And was the most important findings of the study: - The majority of respondents of university students believe that their use of the site "Face book" and exposure to its contents helped them more correlation values, and this contradicts many of the assumptions that the social networking sites do not publish values and the promotion of youth 3. The university students in the majority of them male and female, agree that the site "Face book" helps them to link values, but the female because of their role in society were more strongly in the ability of social networking sites to make them Ertbtun more ambitious values, appreciation of science, self-responsibility to respect. 4. The site "Face book" can not help young people to overcome some of the negative behaviors, if the latter were directed values, and occur in the social environment, which belongs to the university students and they live, what prevents from doing these behaviors are social institutions and culture and traditions and is not social networking sites in general and the site "Face book" in particular.